First Normal School for Men in Guatemala (1875-1918 first stage). Foundation, authorities, teachers, crises and permanent changes - López Rivas, Oscar Hugo; Hernández Ayala, Ana María (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: to establish relevant historical aspects of the foundation, authorities, teachers, crisis and permanent changes of the Normal School in Guatemala, in order to motivate the analysis of the historical development of normalism and the teaching career in the country. Originality/support: The systematization and chronological organization of events that took place in Guatemala since the first attempts to found a Normal School in 1831 and its foundation in 1875, as well as the development of its first stage until 1918, constitute a significant contribution to the history of normalism in the country. The originality is evidenced in the first part of the article, which presents detailed historical data, that is little known to society at large, on the development of the Normal School and the teaching career in Guatemala. The contribution seeks to motivate informed and documented discussion and analysis of the subject. Method: The research work, basis of this article, used documentary methods including the consultation of written sources such as books and magazines of that time. The state of the art was also taken into account, which made it possible to study the existing and accumulated knowledge on the subject. Strategies/information collection: In order to obtain more precise results that would reinforce the documentary review carried out as part of the documentary research method, the interview was used as a strategy for the collection of information. Key actors, such as the principal, graduates of the Normal School for Men, and a researcher of normalism in Guatemala, participated in the interview. Conclusions: The creation of the Normal School for Men in Guatemala marked the beginning of cultural and educational development in the country, had influence at the social level, and its development was limited by the political actions of each government in power. Its founding, development, authorities, teachers, crises and changes have marked the history of both normalism in Guatemala and the teaching career. In addition, the Normal School for Men has given the country professionals who have made history and have contributed to social, educational and academic development.